AN ANALYSIS OF CODE-MIXING IN SPEAKING FOUR CLASS OF FACULTY OF LETTERS IN UNIVERSITAS KRISTEN INDONESIA : A CASE STUDY - Gitta Vania Naulibasa; Masda Surti Simatupang (Prodi Sastra Inggris UKI, 2019)
This research is about code mixing. Code-mixing is the alternation between varieties or codes within words, clauses, or phrases. The use of code-mixing usually happens in people who speak more than one language or also called bilingual or multilingual people. The writer did this research in order to find out the code-mixing cases based on code-mixing theory in the study of sociolinguistics. She took a descriptive method that used two ways of collecting the data, firstly tape-recording and then questionnaires. The respondents of this research are Speaking Four students batch 2013 in Faculty of Letters in Universitas Kristen Indonesia. The reasons why they commit code-mixing, the type of codes that they mixed, and the proportion of female to male students committing code-mixing are the results of this study. There are 73 data which consist of codes that were mixed by the students: parts of speech (49), phrases (7), and question forms (17). The most common user of code-mixing is the noun (part of speech) and WH-question (question form).